Oral Condition of Adolescents who Participated in an Oral Health Program During the First Decade of Life - Amaral, Jaqueline Canova Paludetto [UNESP]; Gawlinski, Bárbara Curi [UNESP]; Duque, Cristiane [UNESP]; Cunha, Robson Frederico [UNESP] (FapUNIFESP (SciELO), 2023)
Objective: To evaluate the oral health of adolescents who participated in an oral health preventive program during the first decade of life. Material and Methods: For the evaluation of dental caries and gingival condition, DMFT and Community Periodontal Index were used, both recommended by the World Health Organization. To verify the occurrence of dental fluorosis, the Dean index was used. Results: Data collection was obtained from 252 patients aged 12 to 16 years. The average DMFT index was 1.14; in relation to the gingival condition, the index of healthy gingival tissue prevailed and the average of this value was 84%, with code 0 being more registered in tooth 11, code 1, more frequently in teeth 16/17 and 36/37 and for last, code 2, in tooth 31 most frequently. Dean's index showed a percentage of 89% of patients without clinical signs of dental fluorosis. Conclusion: Adolescents participating in an oral health preventive program in the first decade of life exhibited very satisfactory results regarding the prevention of caries disease, healthy periodontal condition and reduced prevalence of dental fluorosis.
Keywords: Dental Caries; Oral Health; Preventive Dentistry; Preventive Health Services